تقييم آلية عمل مشاريع التشييد السريع في سورية وفق معايير التشييد السلس - رنا ميّا; ديانا سمير حمد (Tishreen University, 2019)
تقييم آلية عمل مشاريع التشييد السريع في سورية وفق معايير التشييد السلس رنا ميّا ديانا سمير حمد تشكل صناعة البناء التوجّه التطويري لقطاع البناء والتشييد، والذي يعتبر واحداً من القطاعات الاقتصادية الهامة من حيث دوره في تكوين رأس المال الثابت والإنتاج القومي الإجمالي , لكن مازال التأخير في المشاريع الانشائية يأخذ حيّزاً كبيراً من الاهتمام خاصة في الدول النّامية )لما تشكله هذه الظاهرة من ثقل على العملية التنموية  (في القطاع الحكومي والخاص , مما جعل هناك حاجة لإدخال منهجية جديدة تُطوّر الإنتاج في قطاع البناء وفق معايير التشييد السلس بمبادئه وأدواته لتحسين إدارة تنفيذ البناء بتدفق مستمر خالٍ من الضياعات الزمنية. لتحقيق ذلك قمنا بدراسة الوضع الراهن لآلية تنفيذ مشاريع التشييد السريع من خلال تصميم نموذج تقييم مكون من 30 معيار فرعي موزعة على ستة محاور رئيسية وبعد التحليل تبين أن مستوى التطبيق الحالي لمشاريع التشييد السريع في سورية هي قيمة تعبّر عن مستوى تطبيق دون المتوسط (2.5)، فقد حصل محور الضياعات على أدنى نسبة للتطبيق 2.06 وهي حرجة وتؤثر بشكل سلبي على المشروع.  كما أنه تمّ إيجاد دليل الشدة من أجل ترتيب أهمية تطوير معايير تقييم. ولتحديد مصدر الضياعات كونها العامل الأكثر سلبية تم دراسة حالة لأحد مشاريع التشييد السريع في سورية، وتصنيفها بحسب قيمتها المضافة ثم رسم خرائط تدفق المعلومات والموارد) لإظهار الضياعات وتحديد أسبابها بغية إزالتها لتحسين أداء وإنتاجية مشاريع التشييد السريع (وتحقيق مبادئ التشييد السلس. The construction industry is the developmental trend of the construction sector, which is considered one of the important economic sectors in terms of its role in the formation of fixed capital and gross national product. However, delays in construction projects still take a great deal of attention especially in developing countries due to its great impotence in the development process in the public and private sector, This necessitated the introduction of a new methodology that develops production in the construction sector in accordance with the standards of construction with its principles and tools to improve the management of construction implementation with a continuous flow free of time losses. In order to achieve this, we have examined the status of the mechanism for the implementation of rapid construction projects by designing an evaluation model consisting of 30 sub-criteria divided into six main axes. After the analysis, the current application level of the rapid construction projects in Syria is a value that expresses an application level below average 2.5. The focus of the losses was the lowest application rate of 2.06, which is critical and has a negative impact on the project. A robustness manual was also developed to rank the importance of developing evaluation criteria. In order to determine the source of losses as the most negative factor, a case study of a Rapid construction project in Syria was carried out, classified according to its added value, and mapping the flow of information and resources to show the losses and their reasons aiming to give them an end in order to improve Rapid construction projects.